(untitled) (Indian Journal of Public Health Research & Development, 2026)
Antimicrobial resistance (AMR) represents a critical and escalating global public health threat, driven primarily by the overuse and misuse of antibiotics in human medicine, agriculture, and animal production. The emergence and dissemination of multidrug-resistant (MDR) organisms are further accelerated by horizontal gene transfer, environmental reservoirs, and inadequate infection prevention and control practices. Recent global estimates indicate that bacterial AMR was directly responsible for 1.27 million global deaths in 2019 and contributed to 4.95 million deaths, with projections suggesting substantial increases in mortality and economic burden if effective interventions are not implemented. This review summarizes the major molecular mechanisms underlying antimicrobial resistance, including enzymatic drug inactivation, target modification, porin modifications, efflux pump overexpression, and biofilm formation. Innovative approaches, including phage therapy, CRISPR-based antimicrobials, monoclonal antibodies, nanomaterials, vaccination and artificial intelligence (AI) are highlighted as promising next-generation alternatives. Despite scientific advances, the antibiotic development pipeline remains constrained by economic and regulatory challenges. Sustained research and development, strengthened antimicrobial stewardship, global surveillance, and collaborative industry-academic partnerships are essential to preserve existing therapies and ensure future treatment options against MDR pathogens.